Application of Modified Clay Catalysts in Oligomerization of Light Olefins - Raila Toktassyn; B.T. Utelbayev (Chemistry Department, The University of Brawijaya, 2018)
The oligomerization of light olefins to high-octane clean engine fuels is one possible way to solve increased requirements for motor fuels. This paper presents a study of catalytic oligomerization of C2-C4 olefins on Ru-Fe supported pillared clay catalyst with different metallic quantity. The prepared catalysts were characterized by X-ray diffraction, N2 adsorption-desorption at 77K, BET and BJH methods. The BET and BJH methods showed the pillared clay had significantly increased surface area and when an appropriate amount of Ru and Fe were added, the bimetallic alloys were uniformly dispersed on the modified clay surfaces and had an average mesopore size of 4.1 nm. It is indicated that excess metal oxides blocked the surface of bimetallic RuFe/MMC system, resulted in decreased catalytic activity. The low metal content catalysts showed higher oligomerization activity and increasing the Fe content gave selectivity to isomerization reactions.